IMPLEMENTASI UPAYA PENGEMBANGAN KOMPETENSI GURU TK DALAM PEMBUATAN BAHAN AJAR YANG INTERAKTIF DI KECAMATAN SINDANGBARANG KABUPATEN CIANJUR - Fauzi, Ikka Kartika Abbas; Kunaefi, Piping Hendri; Wahyudi, Nendi; Rismawati, Irma; Nursaleh, Ayi (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
Teachers’ ability to design engaging and interactive teaching materials is a critical factor in the success of early childhood education. However, many kindergarten teachers still face challenges in developing instructional resources that match children's developmental characteristics. This issue was also identified at TK Mandala, Sindangbarang District, Cianjur Regency, where most teachers lacked adequate skills in creating innovative and creative teaching materials. This community service program aimed to improve kindergarten teachers’ competence through intensive training and mentoring. The implementation involved administrative preparation, content planning, training sessions, hands-on practice, and evaluation. Data collection techniques included observation, interviews, and documentation of teaching materials created by participants. The results demonstrated significant improvements in teachers’ knowledge, technical skills, and attitudes toward material development. Teachers successfully produced interactive media such as flashcards, thematic posters, flannel boards, and simple digital content. The program also enhanced teachers' motivation, peer collaboration, and willingness to innovate. In conclusion, this community service activity contributed to strengthening the quality of early childhood learning and provided a sustainable impact on teacher professionalism and classroom practice.